Mengungkap Isyarat-Isyarat Sains Dalam Hadis Nabi - Yuri Indri Yani; Yuliharti Yuliharti; Kholil Syu’aib; Mardinal Tarigan; Paini Paini (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Revealing Science Signs in the Prophet's HadithThis study aims to explore the concept of the signs conveyed by the Prophet through his words relating to science or science. In addition, it also presents traditions that give a signal for humans to always develop knowledge in carrying out the duties of the caliph on earth. The method used in this article is in the form of pure literature with the techniques used in collecting data based on documentation through written legacy evidence such as writings or manuscripts, archives, books on opinions, theories, concepts and arguments and related laws. with the formulation of the study problem. Based on this article, it is found that the hadith is very important for humans to study and research the universe and its contents and always instructs humans to develop knowledge for the advancement of human civilization. Where long before the discoveries in the field of science and technology were discovered or scientifically proven, the Messenger of Allah had hinted at his people through his words